Effect of Meconium Stained Liquor on Mode of Delivery and Fetomaternal Outcome at Term - Asma Qayyum, Rubina Iqbal, Huma Mazher (Pakistan Journal of Medical & Health Sciences, 2023)
Background: Meconium-stained amniotic fluid is a major reason for concern for both obstetricians and pediatricians since it raises the risk of birth hypoxia, maternal-asphyxia syndrome, and hospitalizations to the neonatal intensive care unit. Objective: To find the frequency of meconium stained liquor in females presenting in labor at term and to compare the frequency of adverse feto-maternal outcome with or without meconium stained liquor in females presenting in labor at term. Materials & Methods Study Design: Descriptive study SETTING: Department of Obstetrics & Gynecology, Fatima Memorial Hospital Lahore Duration: Six months i.e. 15-12-2020 to 15-6-2021 Data Collection Procedure: A total of 175 females fulfilled the inclusion criteria were included. Then females were followed up in labor room. If meconium stained liquor was observed, then it was noted and female were divided in two groups i.e. with meconium stained liquor and without meconium stained liquor. Mode of delivery was noted. Apgar score was noted and labeled as poor if <7 at 5 minutes. Birth asphyxia and need for NICU admission was noted. Than all these patients were followed up in gynecology wards for 3 days, neonatal mortality was noted, if occurred. Results: In this study frequency of meconium stained liquor in females presenting in labor at term was 51(29.1%). Comparison of feto-maternal outcome in women with and without meconium stained liquor showed that C-section rate (37.3% vs. 18.5%, p-value=0.008), Poor Apgar score (7.8% vs. 1.6%, p-value=0.040), NICU admission (13.7% vs. 3.2%, p-value=0.009), Birth Asphyxia (19.6% vs. 4%, p-value=0.001) and early neonatal mortality (13.7% vs. 3.2%, p-value=0.009) was significantly higher among women with meconium stained liquor. Conclusion: Keeping in mind the results of this study it can be concluded that positive meconium stained liquor had a significantly impact on maternal as well as neonatal outcome. Keywords: Meconium, Stained liquor, C-section, Birth Asphyxia, NICU, Mortality